Effects of 3-indoleacrylic acid on alleviating lipopolysaccharide-induced liver inflammatory damage in laying hens - Qiyue Zhang; Yue Wang; Yanwei Wang; Jielu Yuan; Yaru Wang; Yongqi Zeng; Haihua Zhang; Hui Yang; Qiugang Ma; Donghui Shi; Shimeng Huang (Poultry Science, 2025)
This study investigates the effects of 3-indoleacrylic acid (IAA), a bacterial metabolite of tryptophan, on LPS-induced liver injury in laying hens. The aim is to explore the potential hepatoprotective mechanisms of IAA, particularly through the modulation of inflammatory and antioxidant pathways. A total of 48, 24-week-old No. 6 Jingfen laying hens were randomly divided into four groups of 12 hens each: the CON group (basal diet), IAA group (basal diet + 150 mg/kg IAA), LPS group (basal diet), and IAA+LPS group (basal diet + 150 mg/kg IAA). The feeding period lasted 8 weeks, and at the end of the 8th week, the laying hens in the LPS and IAA+LPS groups were intraperitoneally injected with 0.5 mg/kg LPS. The four groups were uniformly slaughtered and sampled 12 h after LPS injection. The expression of pro-inflammatory cytokines (IL-1β, TNF-α, IL-6) was significantly alleviated (P < 0.05), and antioxidant enzymes (T-SOD, CAT, GSH-PX) were significantly elevated (P < 0.05) in the serum and liver of the IAA+LPS group. Histological analysis revealed reduced hepatocyte necrosis and inflammation in the IAA-treated groups (P < 0.05). Additionally, the activation of MAPK and Toll-like receptor (TLR) signaling pathways was modulated through transcript analyses, thereby reducing inflammation and oxidative stress. In summary, IAA effectively mitigates liver inflammation and oxidative stress through the regulation of MAPK and TLR signaling pathways, providing a promising strategy for improving liver health in hens. This study represents the first report on the application of IAA in poultry, demonstrating its potential as a novel therapeutic agent for alleviating liver injury.